(untitled) (Journal of Science and Technology, 2016)
The electron phonon interaction in a superlattices has been considered using Green function. This approach provides an easy method of obtaining the Absorption coefficient both for electrons and phonon, and also calculating the shift in the ground state energy of electrons in superlattices due to the interaction